PENGARUH FRAUD TRIANGLE SEBAGAI PREDIKTOR KECURANGAN PELAPORAN KEUANGAN - MIA TRI PUSPITANINGRUM; EINDYE TAUFIQ; SATRIA YUDHIA WIJAYA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The purpose of this study is to examine Influence of external pressure, effective monitoring, and rationalitation to financial fraudulent reporting. The sample used in this study is real estate, property, and building construction companies listed on the Indonesia Stock Exchange (BEI) in the period 2016-2017. By using purposive sampling method, it is obtained as many as 57 real-estate, property, and building construction companies as the study sample. The method of analysis used in this study is logistic regression. In this research also include the overall fit model test, hosmer and lemeshow’s test, goodness of fit test, and classification matrix. Results of this study indicate that the effective monitoring and rationalitation are not significant to financial fraudulent reporting, while external pressure is significant to financial fraudulent reporting.